Power productivity of the ground surface - Gutu A.I.; Radgbhandari E. (Problems of the Regional Energetics)
Here there is presented an attempt to estimate the efficiency degree when working with soil surface through the different methods of valorization incident solar radiation. Such technical methods are being analyzed as (solar collectors, photovoltaic cells, solar thermal power plants), power cultures field (bushes, wheat, sunflower, maize, rape, sorghum) as well as microalgae crops. Here is the description of advantages and disadvantages for each group in part out of these three. The technical methods are up to date from the efficiency utilization view-point of industrial area. Microalgae crops are similar to technical methods from this point of view.